1994
DOI: 10.1037/0735-7044.108.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic and acute cocaine treatment on the onset of maternal behavior and aggression in Sprague-Dawley rats.

Abstract: Pregnant rats were treated either throughout gestation (GD 1-20) with 30 mg/kg per day (chronic cocaine) or with one 15-mg/kg dose immediately following parturition (acute cocaine). Chronic and acute cocaine treatment delayed or diminished the postpartum onset of some components of maternal behavior, and chronically treated dams were significantly more aggressive toward a male intruder than acute cocaine-treated or saline-treated dams. Cocaine increased the latency to crouch over pups and decreased crouch dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
141
6
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(165 citation statements)
references
References 46 publications
15
141
6
3
Order By: Relevance
“…Their offspring are born blind, unable to thermoregulate, defecate, urinate, or protect themselves from attack (Numan, 1994), thus needing considerable maternal care to survive (Stern, 1997). Behaviorally and neurologically, maternal behavior in the rat has also been relatively well characterized (Numan, 1994;Pedersen, Ascher, Monroe, & Prange, 1982;Pedersen, Caldwell, Walker, Ayers, & Mason, 1994) so that any insult to normal maternal behavior can be easily determined.Maternal separation studies also support a rat intergenerational model of behavior showing that cross-fostering results in behavior of offspring similar to behavior of rearing dams, suggesting a nongenetic transmission of behavior (Francis, Diorio, Liu, & Meaney, 1999;Liu, Caldji, Sharma, Plotsky, & Meaney, 2000), which among other data led us to investigate the presence of intergenerational effects of cocaine use.As far as the literature to date, there is general agreement that acute cocaine treatment in rat dams disrupts both early onset and established pup-directed maternal behavior, while increasing locomotor behavior and stereotypies (Johns, Nelson, et al, 1998;Johns, Noonan, Zimmerman, Li, & Pedersen, 1994;Kinsley et al, 1994; Zimmerberg & Gray, 1992). Significant disruptions in maternal behavior following chronic gestational cocaine treatment during pregnancy were reported for the onset or very early post-partum period, and these dams did not display the hyperactivity often seen in acutely treated dams (Heyser, Molina, & Spear, 1992;Kinsley et al, 1994;Peeke, Dark, Salamy, Salfi, & Shah, 1994; Vernotica, Lisciotto, Rosenblatt, & Morrell, 1996).…”
mentioning
confidence: 99%
“…Their offspring are born blind, unable to thermoregulate, defecate, urinate, or protect themselves from attack (Numan, 1994), thus needing considerable maternal care to survive (Stern, 1997). Behaviorally and neurologically, maternal behavior in the rat has also been relatively well characterized (Numan, 1994;Pedersen, Ascher, Monroe, & Prange, 1982;Pedersen, Caldwell, Walker, Ayers, & Mason, 1994) so that any insult to normal maternal behavior can be easily determined.Maternal separation studies also support a rat intergenerational model of behavior showing that cross-fostering results in behavior of offspring similar to behavior of rearing dams, suggesting a nongenetic transmission of behavior (Francis, Diorio, Liu, & Meaney, 1999;Liu, Caldji, Sharma, Plotsky, & Meaney, 2000), which among other data led us to investigate the presence of intergenerational effects of cocaine use.As far as the literature to date, there is general agreement that acute cocaine treatment in rat dams disrupts both early onset and established pup-directed maternal behavior, while increasing locomotor behavior and stereotypies (Johns, Nelson, et al, 1998;Johns, Noonan, Zimmerman, Li, & Pedersen, 1994;Kinsley et al, 1994; Zimmerberg & Gray, 1992). Significant disruptions in maternal behavior following chronic gestational cocaine treatment during pregnancy were reported for the onset or very early post-partum period, and these dams did not display the hyperactivity often seen in acutely treated dams (Heyser, Molina, & Spear, 1992;Kinsley et al, 1994;Peeke, Dark, Salamy, Salfi, & Shah, 1994; Vernotica, Lisciotto, Rosenblatt, & Morrell, 1996).…”
mentioning
confidence: 99%
“…Various rodent studies have reported numerous effects of prenatal exposure to cocaine on subsequent adolescent and adult play, social, and aggressive behaviors [23,38,52,53]. To our knowledge, no prior study has examined the differential effects of prenatal cocaine exposure and rearing condition on next generation offspring pup-induced maternal behavior, although we have recently reported differences in postpartum maternal behavior following prenatal cocaine exposure and altered rearing conditions [17].…”
Section: Introductionmentioning
confidence: 82%
“…The intermittent schedule was modeled after a previous study examining behavioral effects of prenatal cocaine exposure on offspring [19] and is designed to model intermittent usage patterns in humans. The IC treatment regimen was employed in addition to the CC treatment as previous research indicated differences in maternal behavior following either acute or intermittent cocaine treatment in dams [20,23,25,50,55] accompanied by differences in oxytocin (OT) system dynamics following the different treatment regimens [7,22]. UN dams were weighed and handled daily, but received no drug treatment.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations